Revitalization Kasukano Inare: Cultural and Religious Perspectives on the Muna Tribe - Sopiandy, Dede; Umpi, Ridwan; Erni, Erni; Putra, Zulfikar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to explore the revitalisation of Kasukano Inare, a health-focused zacar or covenant among the Muna Tribe. Within a cultural and religious context, the research analyses how this tradition serves as an instrument to maintain community health and strengthen social ties. This research uses a qualitative approach with ethnographic methods. Data collection was conducted through observation, in-depth interviews, and document studies. Observations were conducted to observe the implementation of the Kasukano Inare ritual, in-depth interviews were conducted with traditional leaders, religious leaders, and the Muna people, and document studies were conducted to analyse written sources related to Kasukano Inare. The collected data was then analysed qualitatively with the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that Kasukano Inare not only plays a role in physical health aspects, but also as a spiritual tool that connects individuals to the community and ancestral traditions. In addition, there are dynamics between modern and traditional values that influence the implementation of this agreement. The findings are expected to provide new insights into the importance of cultural and religious integration in public health practices, as well as encourage efforts to preserve local traditions amidst modernisation. The conclusion of this study is that the Kasukano tradition is a manifesta